Model-Based Development and Evolution of Information Systems A Quality Approach - Krogstie, John.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2012)
There is no single approach to modelling and model-based systems development that is best for all possible situations. Therefore, a high-level overview is needed in order to evaluate the options and identify the optimal approach. This unique textbook/reference introduces and describes in detail the SEQUAL framework for understanding the quality of models and modelling languages, including the numerous specialisations of the generic framework, and the various ways in which this can be used for different applications. Examples are provided from the application of SEQUAL in industrial and governmental settings. Topics and features: Contains case studies, chapter summaries, review questions, problems and exercises throughout the text, in addition to Appendices on terminology and abbreviations Presents a thorough introduction to the most important concepts in conceptual modelling, including the underlying philosophical outlook on the quality of models Describes the basic tasks and model types in information systems development and evolution, and the main methodologies for mixing different phases of information system development Provides an overview of the general mechanisms and perspectives used in conceptual modelling Predicts future trends in technological development, and discusses how the role of modelling can be envisaged in this landscape This didactic guide is essential reading for postgraduate students of computer science, software engineering and information systems wishing to learn more about conceptual modelling in their preparation for professional practice. Developers of information systems will also find the book an ideal reference to support their professional activity. Dr. John Krogstie is a Professor of Information Systems in the Department of Computer and Information Science at the Norwegian University of Science and Technology, Trondheim, Norway.
Introduction -- Methodologies for Computerised Information Systems Support in Organisations -- Modeling Languages: Perspectives and Abstraction Mechanisms -- Quality of Models -- Quality of Modelling Languages -- Specialisations of SEQUAL -- Applications of SEQUAL -- Summary and Outlook -- Terminology -- List of Abbreviations -- Cases.
Keywords: Computer science; Computer simulation; Information Systems; Management information systems; Computer Science; Simulation and Modeling; Management of Computing and Information Systems; Business Information Systems